Admission Glucose Levels May Increase the Risk for Early Neurological Deterioration in Females With Acute Ischemic Stroke - Huang, Zhi-Xin; Huang, Yan; Zeng, Jie; Hao, Hong; Petroski, Greg F.; Lu, Haike; Liu, Xintong; Liu, Zhenguo (Frontiers in Neurology, 2020)
Background and Purpose: Early neurological deterioration (END) is associated with poor outcome for patients with acute ischemic stroke (AIS). Patients with hyperglycemia have increased risk for stroke, and tend to have poor outcome with and without diabetes after stroke. The present study aimed to determine if blood glucose was associated with END and if sex difference was present in development of END in AIS patients. Methods: 220 consecutive patients with AIS with recanalization treatment between 2012 and 2015 were screened for this retrospective study. After exclusion, 213 patients were included for analysis. Propensity score matching was used for normalization of variables (stroke severity, symptom onset to treatment, and treatment methods). Results: END was present in 68 patients (31.9%). Multivariate regression analysis indicated that the risk of END was significantly lower in women with AIS than men (P<0.001), and admission glucose level was independently associated with END for all patients (P<0.001). However, subgroup analysis showed that glucose levels were significantly associated with END only in women (P=0.008). When the cutoff value of 5.95 mmol/L was used, the admission glucose level had significant value for END prediction with a sensitivity of 100% and a specificity of 53% in female patients, but not in males. Conclusions: The data demonstrated that sex difference was present for the development of END in AIS patients with increased risk for males. The present study also showed that admission glucose level was an important factor for prediction of END for female patients with AIS.